Identifikasi Jamur Penyebab Onychomycosis Pada Kerokan Kuku Pekerja Bangunan Di Desa Bontokassi Kecamatan Parangloe Kabupaten Gowa - Zulfikar Ali Hasan; Radiatul Adawiyah; Nurlia Naim; Zulfian Armah (Lontara Journal of Health Science and Technology, 2022)
Onychomycosis is a disease caused by dermatophyte and non-dermatophyte fungi that can attack human nails. Work environment, personal hygiene of workers, age and length of work can increase the risk of Onychomycosis. This study aims to identify the fungi that cause Onychomycosis on the nails of construction workers. This research is descriptive observational and using purposive sampling technique. This study used 2 methods of examination, namely directly and indirectly using 20% KOH and planting on Sabouraud Dextrose Agar culture media. The results of the identification of 15 samples using 20% KOH, found 1 (6.67%) positive sample with the discovery of hyphae and spores while 14 (93.3%) other samples were negative. The results of the identification on Sabouraud Dextrose Agar media that had been incubated at 37 oC for 3-5 days, it was found that 15 (100%) samples were positive for fungal infection. The Non-Dermatophyte, namely the discovery of 6 samples (40%) of Aspergillus Sp fungi and 5 samples of Penicillium Sp fungi (33.33%) and the discovery of Dermatophyte fungi, namely Trichopyton sp fungi as many as 3 samples (20%) and Epidermophyton sp as much as 1 sample (6.67%).